The determination of labour productivity for a selected construction operation i.e. plastering work for a housing project / Norlida Saad Md. Saad - Md. Saad, Norlida Saad (1992)
Construction is such a vast/ fragmented, and complex industry that it Is hard to identify and define the problem of productivity and cost effectiveness, what more to resolve them. The objective of this research is to determine the labour productivity for plastering work and to identify the factors affecting its productivity. Observations and monitoring were carried out on four crews. The measurement task was done dally at the end of the work shift. Findings indicated that the output, hence productivity was affected by factors such as experience (level of skills), salary, work conditions and management. Recommendations towards productivity improvements are forwarded from the findings.